GAMBARAN PERILAKU MENYIKAT GIGI DI MESS (Jurnal Kesehatan Siliwangi, 2021)
Unclean oral and dental hygiene and poor tooth brushing behavior as well as tooth brushing techniques that are still not good and correct. The purpose of this study is to find out the description of the teeth brushing behavior of a Mess personnel and the characteristics of the residents at a Mess.This research method is a descriptive study using a frequency distribution table. The population of this study was 22 people. Sampling was done by filling out google forms and analyzed using cross tabulation. The results show that the teeth brushing behavior of personel at a Mess is still not good with a moderate result of 72.7%, and characteristics based on male gender (81.8%), based on age, dominated by ages 26-35 (52 .5%), based on education diploma in health (31.8%) and based on occupation dominated by TNI (68.2%). The behavior of brushing teeth is still not good and should be further improved because the percentage for moderate criteria is 72.7%.